Instrument engineers' handbook. - Liptak, Bela G. (Butterworth Heinemann, 1995)
Instrument Engineers' Handbook, Third Edition: Process Control provides information pertinent to control hardware, including transmitters, controllers, control valves, displays, and computer systems. This book presents the control theory and shows how the unit processes of distillation and chemical reaction should be controlled.Organized into eight chapters, this edition begins with an overview of the method needed for the state-of-the-art practice of process control. This text then examines the relative merits of digital and analog displays and computers. Other chapters consider the basic ind.